Unilateral Relapsing Primary Angiitis of the CNS: An Entity Suggesting Differences in the Immune Response Between the Cerebral Hemispheres. Issue 2 (5th March 2021) - AbdelRazek, Mahmoud A.; Hillis, James M.; Guo, Yanjun; Martinez-Lage, Maria; Gholipour, Taha; Sloane, Jacob; Cho, Tracey; Matiello, Marcelo
Abstract : Objective: To determine whether studying patients with strictly unilateral relapsing primary angiitis of the CNS (UR-PACNS) can support hemispheric differences in immune response mechanisms, we reviewed characteristics of a group of such patients. Methods: We surveiled our institution for patients with UR-PACNS, after characterizing one such case. We defined UR-PACNS as PACNS with clinical and radiographic relapses strictly recurring in 1 brain hemisphere, with or without hemiatrophy. PACNS must have been biopsy proven. Three total cases were identified at our institution. A literature search for similar reports yielded 4 additional cases. The combined 7 cases were reviewed for demographic, clinical, imaging, and pathologic trends. Results: The median age at time of clinical onset among the 7 cases was 26 years (range 10–49 years); 5 were male (71%). All 7 patients presented with seizures. The mean follow-up duration was 7.5 years (4–14.1 years). The annualized relapse rate ranged between 0.2 and 1. UR-PACNS involved the left cerebral hemisphere in 5 of the 7 patients. There was no consistent relationship between the patient's dominant hand and the diseased side. When performed (5 cases), conventional angiogram was nondiagnostic. CSF examination showed nucleated cells and protein levels in normal range in 3 cases and ranged from 6 to 11 cells/μL and 49 to 110 mg/dL in 4 cases, respectively. All cases were diagnosed with lesional biopsy, showing lymphocytic type of vasculitis of the small- and medium-sized vessels. Patients treated with steroids alone showed progression. Induction therapy with cyclophosphamide or rituximab followed by a steroid sparing agent resulted in the most consistent disease remission. Conclusions: Combining our 3 cases with others reported in the literature allows better clinical understanding about this rare and extremely puzzling disease entity. We hypothesize that a functional difference in immune responses, caused by such discrepancies as basal levels of cytokines, asymmetric distribution of microglia, and differences in modulation of the systemic immune functions, rather than a structural antigenic difference, between the right and left brain may explain this phenomenon, but this is speculative.